COMPARISON OF CURB-65 AND PNEUMONIA SEVERITY INDEX FOR PREDICTING INTENSIVE CARE UNIT ADMISSION AND IN-HOSPITAL MORTALITY IN ADULTS WITH COMMUNITY-ACQUIRED PNEUMONIA: A PROSPECTIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Community-acquired pneumonia (CAP) remains one of the leading causes of hospitalization and mortality worldwide despite advances in antimicrobial therapy and supportive care. Early identification of patients at high risk for adverse outcomes is essential for timely escalation of treatment and appropriate utilization of healthcare resources. Among the available prognostic tools, the Pneumonia Severity Index (PSI) and CURB-65 are the most widely recommended; however, their comparative performance in predicting clinically meaningful outcomes in Indian patients remains inadequately explored. This study compared the predictive accuracy of PSI and CURB-65 for intensive care unit (ICU) admission and in-hospital mortality among adults hospitalized with CAP. Methods: A prospective observational study was conducted in the Department of General Medicine, L.N. Medical College and Research Centre, Bhopal, India. Consecutive adult patients diagnosed with community-acquired pneumonia were enrolled after fulfilling predefined inclusion and exclusion criteria. Clinical history, physical examination, laboratory investigations, chest radiography, and microbiological findings were recorded at admission. CURB-65 and PSI scores were calculated for every patient. The primary outcomes included ICU admission and in-hospital mortality. Secondary outcomes included ventilatory support requirement, duration of hospital stay, and clinical status at 48-hour reassessment. Receiver operating characteristic (ROC) curve analysis was performed to compare the discriminatory ability of both scoring systems. Results: Both CURB-65 and PSI demonstrated significant associations with ICU admission, requirement for ventilatory support, prolonged hospitalization, and in-hospital mortality. Increasing scores in both systems corresponded to progressively higher risks of adverse clinical outcomes. PSI demonstrated superior discriminatory performance for mortality prediction, whereas CURB-65 showed comparable predictive ability for ICU admission with considerably greater ease of bedside application. ROC curve analysis confirmed good predictive accuracy for both scoring systems. The simplicity and rapid applicability of CURB-65 make it particularly valuable in emergency departments and resource-limited healthcare settings. Conclusion: Both CURB-65 and PSI are effective prognostic tools for patients with community-acquired pneumonia. Although PSI provides slightly better risk stratification for mortality, CURB-65 offers comparable clinical utility with substantially greater simplicity. Considering its ease of use and minimal requirement for laboratory variables, CURB-65 represents an efficient bedside scoring system for early triage and treatment decisions, particularly in resource-constrained settings.